The practice of copying in making knowledge in Early Modern Europe: an introduction. Issue 3 (3rd July 2019) - Fransen, Sietske; Reinhart, Katherine M.
Abstract: Though the study of copying, imitation, forgery, and reproduction have a long lineage in the history of art, this special issue, and its introduction, seek to investigate the role of copying texts, and especially images, in the process of making new knowledge in the Early Modern period. By looking at a wide variety of images produced in contexts such as artist workshops, learned societies, and publishing houses, and compared with the texts and terminologies of copying and knowledge that surround them, we are not only expanding the scope of when and where copying takes place but also, and especially, emphasizing its importance to the process of creating knowledge. Copying—both its process and how we understand it—has not been a stable concept, and this introduction digs deeper into how Early Modern artists and natural philosophers conceived of and implemented this practice.